2021
DOI: 10.1002/ajhb.23694
|View full text |Cite
|
Sign up to set email alerts
|

Movement behaviors in short versus adequate nocturnal sleepers: A compositional analysis of preschoolers

Abstract: Background: Accruing adequate daily amounts of time spent on movement behaviors (physical activity (PA), sedentary behavior (SB), and sleep) in childhood has been associated with positive short and long-term health outcomes.Nonetheless, how waking time is distributed across PA and SB among preschoolers who are short and adequate sleepers at night is unknown. Aim: This study investigated: (1) if there are differences in a movement behaviors composition among adequate and short nocturnal sleepers; and (2) the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Indeed, since early ages, boys are culturally more exposed to moderate‐vigorous intense activities, that are associated with a better sleep quantity and quality (Ghrouz et al, 2019; Janssen et al, 2020; Kredlow et al, 2015), preventing the excessive weight gain during this age. Moreover, those that remain sleeping for longer periods, are less likely to excessive food intake (Poggiogalle et al, 2016), and are also more likely to be engaged in PA along the day (Gába et al, 2020; Souza et al, 2021), contributing to a reduced BMIz score. Nonetheless, these findings should be interpreted with caution, as children present greater sleep time variabilities at young ages (Bathory & Tomopoulos, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, since early ages, boys are culturally more exposed to moderate‐vigorous intense activities, that are associated with a better sleep quantity and quality (Ghrouz et al, 2019; Janssen et al, 2020; Kredlow et al, 2015), preventing the excessive weight gain during this age. Moreover, those that remain sleeping for longer periods, are less likely to excessive food intake (Poggiogalle et al, 2016), and are also more likely to be engaged in PA along the day (Gába et al, 2020; Souza et al, 2021), contributing to a reduced BMIz score. Nonetheless, these findings should be interpreted with caution, as children present greater sleep time variabilities at young ages (Bathory & Tomopoulos, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, all paths presented in the emergent patterns are direct or indirectly related to TPA. Previous research has shown that preschoolers with short sleep duration spend more time being sedentary, than those who comply with sleep recommendations (G aba et al, 2020;Souza et al, 2021). As postulated by the theory of energy conservation, short sleep duration is related to excessive energy expenditure to keep one alert, when it was supposed to sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations